Hard metal lung disease: importance of cobalt in coolants. Issue 9 (September 1980) - Sjögren, I; Hillerdal, G; Andersson, A; Zetterström, O
Abstract : Four patients were found to react to occupational exposure to grinding of hard metal (tungsten carbide). Three of the patients had symptoms and signs compatible with an allergic alveolitis, the symptoms disappearing and the chest radiograph clearing when they were absent from work for a few months. Re-exposure to the offending agent led to new signs and symptoms. The first patient was re-exposed twice and each time reacted a little more seriously. After the last episode her chest radiograph has not cleared completely, in contrast to the first two times. The fourth patient had more typical occupational asthma. All the cases occurred in the part of the factory where air concentrations of cobalt were the lowest. The cobalt there is dissolved in the coolant necessary for grinding the hard metal. It occurs mainly in the ionised form, which is known to react with proteins and therefore presumably acts as a hapten. Protective measures, including choosing a coolant with minimal ability to dissolve cobalt and an effective exhaust system, should minimise the risk of this occupational disease in the future.